2017
DOI: 10.1002/2017gl074881
|View full text |Cite
|
Sign up to set email alerts
|

Quasilinear analysis of saturation properties of broadband whistler mode waves

Abstract: Saturation properties of parallel propagating broadband whistler mode waves are investigated using quasilinear theory. By assuming that the electron distribution stays bi‐Maxwellian, we combine the previously obtained energy equation of quasilinear theory with wave equation to self‐consistently model the excitation of broadband whistler waves. The resulting evolution profile of wave intensity, spectrum, and electron temperature are consistent with those from particle‐in‐cell (PIC) simulations. We obtain the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 30 publications
11
32
0
Order By: Relevance
“…The dependence of the saturated whistler wave amplitude on the initial maximum growth rate is similar to the one established by Tao et al (2017) in the quasi-linear analysis of the classical temperature-anisotropy instability (Sagdeev & Shafranov 1960;Kennel & Petschek Figure 7. Panel (a) presents the saturated whistler wave amplitude versus initial normalized electron heat flux, as found in the first set of simulations performed at βc = 1 and various initial values of uc/vA and qe/q0 (Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…The dependence of the saturated whistler wave amplitude on the initial maximum growth rate is similar to the one established by Tao et al (2017) in the quasi-linear analysis of the classical temperature-anisotropy instability (Sagdeev & Shafranov 1960;Kennel & Petschek Figure 7. Panel (a) presents the saturated whistler wave amplitude versus initial normalized electron heat flux, as found in the first set of simulations performed at βc = 1 and various initial values of uc/vA and qe/q0 (Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…The dependence of ( B∕B) 2 on max can be roughly written as ( B∕B) 2 ∝ max , where the slope varies between 0.70 and 0.76 ( Figure 6). This value is close to the quasi-linear theory results obtained by Tao et al (2017), who showed that ( B∕B) 2 = 0.17 0.76 max with only hot electrons.…”
Section: The Dependence Of Wave Amplitude On Plasma Parameterssupporting
confidence: 91%
“…PIC codes are used to investigate the self‐consistent mechanism of wave generation and growth in the radiation belts, such as chorus generation and enhancement (Fu et al, , ; Lu et al, ), whistler instability effects (Fan et al, ; Yoon et al, ) and saturation (Wu et al, ), and magnetosonic wave excitation (Chen et al, ) and propagation (Min et al, ). PIC codes are also used to test the validity of the quasilinear theory (e.g., Camporeale, ; Tao et al, ) and for computing spacecraft charging in the radiation belts (Delzanno et al, ; Lucco Castello et al, ). Hybrid codes in which the dense cold electrons are treated as a fluid while the resonant electrons are treated as super particles (PIC based).…”
Section: New Radiation Belt Modeling Capabilities and The Quantificatmentioning
confidence: 99%